The Time of the Insult/Triggering Event in Primary Osteosarcoma and Ewing's Sarcoma of Bone as Determined by Incubation Period Modeling and Age Distribution of Such Malignancies. (11th March 2015) - Loder, Randall T.; Sabatino, Meagan
Abstract : The time for the triggering event in neoplasms can be estimated using incubation period modeling techniques. We applied these techniques to primary osteosarcoma and Ewing's sarcoma of bone using the Surveillance Epidemiology and End Results database for all cases of osteosarcoma or Ewing's sarcoma of bone from 1993 through 2010. Secondary neoplasms were excluded. The age at diagnosis, gender, ethnicity, and anatomic location were collected. The time (x t ) of the insult/triggering event was calculated using the best fit frequency distribution of age at diagnosis. There were 4, 356 patients with osteosarcoma and 1, 832 patients with Ewing's sarcoma. The Pearson IV distribution was the best fit for both osteosarcoma (r 2 = 0.987 ) and Ewing's sarcoma (r 2 = 0.99 ). For these distributionsx t is −0.7 years of age (4 weeks after conception) for Ewing's sarcoma, 0.45 years for long bone osteosarcoma, and 10.4 years for parosteal osteosarcoma. This confirms the genetic etiology of Ewing's sarcoma since anx t is 4 weeks after conception. Long bone osteosarcoma is not entirely genetic, asx t was 0.4 years for conventional osteosarcoma and 10.4 years for parosteal osteosarcoma. The etiologies for those two different types of osteosarcoma are thus different.